1995
DOI: 10.1007/bf00020881
|View full text |Cite
|
Sign up to set email alerts
|

Transgene-mediated auxin overproduction in Arabidopsis: hypocotyl elongation phenotype and interactions with the hy6-1 hypocotyl elongation and axr1 auxin-resistant mutants

Abstract: Transgenic Arabidopsis thaliana plants constitutively expressing Agrobacterium tumefaciens tryptophan monooxygenase (iaaM) were obtained and characterized. Arabidopsis plants expressing iaaM have up to 4-fold higher levels of free indole-3-acetic acid (IAA) and display increased hypocotyl elongation in the light. This result clearly demonstrates that excess endogenous auxin can promote cell elongation in a whole plant. Interactions of the auxin-overproducing transgenic plants with the phytochrome-deficient hy6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 36 publications
(50 reference statements)
10
114
0
3
Order By: Relevance
“…IAOx was proposed as a key intermediate in IAA biosynthesis on the basis of several observations. (i) Overexpression of CYP79B2 leads to high auxin phenotypes such as elongated hypocotyls similar to known auxin overproduction lines such as yuc1D and iaaM overexpression lines (8,33). (ii) Inactivation of SUR1 or SUR2 blocks IG biosynthesis, and leads to auxin overproduction phenotypes because of the diversion of IAOx to IAA synthesis (9,10).…”
Section: Biosynthesis Of Iaoxmentioning
confidence: 89%
“…IAOx was proposed as a key intermediate in IAA biosynthesis on the basis of several observations. (i) Overexpression of CYP79B2 leads to high auxin phenotypes such as elongated hypocotyls similar to known auxin overproduction lines such as yuc1D and iaaM overexpression lines (8,33). (ii) Inactivation of SUR1 or SUR2 blocks IG biosynthesis, and leads to auxin overproduction phenotypes because of the diversion of IAOx to IAA synthesis (9,10).…”
Section: Biosynthesis Of Iaoxmentioning
confidence: 89%
“…Indeed, it is possible that the substances controlled by the Rms2 and Rms3 genes are involved in the regulation of IAA level and that these regulatory processes may operate prior to, or independently of, the action of the Rms4 gene. The axrl mutant of Arabidopsis also has increased branching (Lincoln et al, 1990) and elevated IAA levels (Romano et al, 1995), but whether graft-transmissible factors are involved in the increased branching and reduced IAA response of these plants is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results strongly suggest involvement of a light-induced decrease in IAA level in the light inhibition of plant cell elongation. Using IAA overproducing transgenic Arabidopsis lines, Romano et al (1995) demonstrated that the regulation of hypocotyl elongation by auxin and light are independent, since IAA overproducing plants exhibited normal responses to light. The question of the physiological significance of light-regulated IAA level is thus still open.…”
Section: Light and Auxinmentioning
confidence: 99%